Cultural sustainability thresholds to measure the mauri of Indigenous Māori values impacted by geothermal engineering projects - Nona Taute; Te Kipa Kēpa Brian Morgan; Jason Ingham; Rosalind Archer; Tumanako Fa'aui (Environmental and Sustainability Indicators, 2023)
Aotearoa New Zealand's current geothermal laws require that any engineering utilisation of geothermal resources includes an assessment of how Māori values are impacted, being the values held by the country's Indigenous Peoples. A series of wānanga (Māori-based workshops) were conducted with Māori participants to develop a list of Māori values pertinent to geothermal development, followed by a companion list of corresponding sustainability indicators that defined measurable parameters as quantitative representations of these Māori values. For each indicator, sustainability thresholds were developed, which described three possible impacted indicator states that constituted denigrated, neutral, and enhanced levels of mauri respectively, where mauri was a proposed measure of wellbeing. The information contained in the thresholds provided a means to numerically assess the extent to which an engineering project in Aotearoa would sustain the wellbeing of the listed indicators, and in turn the listed Māori values. The insights within the thresholds may be used by other researchers to develop thresholds specific to other indigenous cultures around the world and empower such cultures in their countries' own geothermal industries.